(untitled) - Prof. Dr. Martin Gläser, Stuttgart; Prof. Dr. Georgios Gounalakis, Marburg; Prof. Dr. Thomas Hess, München; Prof. Dr. Frank Lobigs, Dortmund; Prof. Dr. Christoph Neuberger, München; Prof. Dr. Insa Sjurts, Friedrichshafen (MedienWirtschaft, 2018)
MedienWirtschaft - Zeitschrift für Medienmanagement und Medienökonomie